Short communication. Phytoseiid mites (Acari: Phytoseiidae) from apple trees in Rio Negro, Argentina - Ruiz, M.G.=700 1 Sosa, D.H.; Speranza, C.; Lofego, A.C.; De Morales, G.J.; Fernandes, O.A.
(Es, En)
ilus., 7 ref.
Keywords: ACAROS NOCIVOS; DEPREDADORES; MANZANA; CONTROL BIOLOGICO; EUSEIUS; METASEIULUS; NEOSEIULUS; ESPAÑA